THE CONCEPTS OF "LION", "WOLF", AND "FOX" IN ENGLISH AND KAZAKH LANGUAGES: A COMPARATIVE ANALYSIS OF PEOPLE NAMES: THE CONCEPTS OF "LION", "WOLF", AND "FOX" IN ENGLISH AND KAZAKH LANGUAGES: A COMPARATIVE ANALYSIS OF PEOPLE NAMES - Nysanova, Kuralay (Журнал иностранных языков и лингвистики, 2025)
In both English and Kazakh linguistic traditions, the use of animal names as personal identifiers is a noteworthy phenomenon that embodies particular qualities or attributes associated with the respective animals. This article aims to delve into the cultural significance and connotations of the terms "Lion," "Wolf," and "Fox" within both languages. We will examine how these animal names are perceived and utilized in naming practices, highlighting their symbolic meanings and the cultural contexts that inform their adoption as personal names. Through this exploration, we seek to illuminate the interplay between language, culture, and identity as reflected in the use of these animal-inspired names.